St. Kitts and Nevis : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for St. Kitts and Nevis. (IMF Staff Country Reports; Country Report ;, 2021)
St. Kitts and Nevis entered the Covid-19 pandemic from a position of fiscal strength following nearly a decade of budget surpluses. A significant part of the large CBI revenues was prudently saved, reducing public debt below the regional debt target of 60 percent of GDP and supporting accumulation of large government deposits.